Ethnosocial Learning Based on Socio-Cultural Literacy: An Exploratory Study in Elementary School - Elya Umi Hanik; Sintha Sih Dewanti; Ibrahim (Journal of Integrated Elementary Education)
This research aims to explore the application of the ethnic social learning model, which is grounded in socio-cultural literacy, at the Miftahul Ulum Elementary School in Loram Kudus. The study utilizes an exploratory qualitative approach to understand phenomena where existing information is scarce comprehensively. This research includes fieldwork, with researchers conducting direct observations at the site to obtain and collect pertinent data. Data collection techniques employed in this study included observation, interviews, and documentation methods. Credibility was assessed through three forms of triangulation to ensure the validity of the data: source, technique, and time. Data analysis followed the Miles and Huberman model, which entails data reduction, data presentation, and drawing conclusions alongside verification processes. The findings underscore the effectiveness of the ethnic social learning model in integrating local cultural values, social literacy, and interpersonal interactions into the educational process. This approach cultivates educational experiences that are both contextually relevant and meaningful. A notable aspect of the research is incorporating the local tradition 'Ampyang Maulid' into the Miftahul Ulum curriculum, which is reflected in both curricular and extracurricular activities. This strategy reinforces character development among students and enhances their cultural awareness and social literacy skills. The study concludes with practical recommendations, including the need for teacher training, improvements in educational facilities, and the encouragement of community collaboration. Overall, this research offers significant theoretical insights into advancing the concept of ethnic social learning within the Indonesian educational context.